2020
DOI: 10.3390/su12030792
|View full text |Cite
|
Sign up to set email alerts
|

Managing Sustainable Urban Tourism Development: The Case of Ljubljana

Abstract: The interest in sustainable urban development and sustainable tourism development is growing. Yet, according to our knowledge, only a limited number of studies combining those two areas exist, and the holistic model for sustainable urban tourism development has not been introduced. Our study aims to integrate sustainable urban development scientific area with sustainable tourism development scientific area and to integrate and advance the existing models for sustainable urban tourism development. As a method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Earlier studies that looked at sustainable tourism implementation highlighted that local and central government should play a relevant role in managing, including financially, tourism flows. They enjoy huge influence on related policy areas that affect land take and spatial planning, such as (tourism) infrastructure, real estate pressure or residentialism, transport and smartization, planning of natural areas and parks, as well as recreational economic zoning for the region [56,70,71]. Thus, land use planning assumes tourism as an integral factor of sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies that looked at sustainable tourism implementation highlighted that local and central government should play a relevant role in managing, including financially, tourism flows. They enjoy huge influence on related policy areas that affect land take and spatial planning, such as (tourism) infrastructure, real estate pressure or residentialism, transport and smartization, planning of natural areas and parks, as well as recreational economic zoning for the region [56,70,71]. Thus, land use planning assumes tourism as an integral factor of sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, innovative technologies within the smart city will enable citizens to feel at ease and develop digital city management that minimizes its environmental impact. The concept of the "smart city" is based on intelligent urban management with minimal human interaction [181][182][183].…”
Section: Automated Content Analysis Results For Articles From 5/1996 mentioning
confidence: 99%
“…It can be concluded that future researches should be focused on monitoring of the CSR and sustainable development impact on the economy. It will also be necessary to take into account the issues related to COVID-19, which has a significant impact on changes in the field of work organization, economics, and the operation of the company itself and citizen wellbeing, especially in cities that have to be transformed not only in smarter and more sustainable ways [127], but also safe from crime, natural disasters, pandemic, and other catastrophes [128,129]. The virus pandemic is leading to a faster digital transformation, and various digital platforms are increasingly being developed to enable work and education from home [130].…”
Section: Discussionmentioning
confidence: 99%